IMIGRANTES E SEUS “ACESSOS” ÀS POLÍTICAS DE SEGURIDADE SOCIAL NO BRASIL (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2024)
This research explores the health and social security guarantees offered to immigrants in Brazil. This topic is relevant due to the high migratory flow that has historically occurred in Brazil, as well as the significant presence of immigrants who contribute to the country's economic development. The effectiveness and adequacy of protection for immigrants in the area of ​​social assistance and social security not only benefits this population, but also helps to reduce known social risks. The methodology used in this research was logical-deductive in nature, based on analyses of legislation and specialized literature. The purpose was to offer a comprehensive and objective view of the importance of ensuring the protection of immigrants in Brazil through social assistance and social security policies. Among the main results obtained, we highlight the need to guarantee access to social assistance for all immigrants in the country, including those who do not have legal residence; the provision of social security protection to immigrants who contribute to the official Brazilian social security system; and the expansion of international social security agreements that allow the summation of contribution periods between the nations in which the immigrant worked. Thus, the research raises the issue of the importance of the State offering social support to immigrants who choose Brazil as their destination. This is due to the importance of the workforce and economic growth provided by immigrants, and it is essential that society assumes the responsibility of guaranteeing them minimum security.